The Philosophy of Liberation in the Qur’an: An Educational Reading through Critical Pedagogy - Inayati, Nurul latifatul; Putra , Muhammad Irwan; Khamami, Khamami; Nirwana, Andri (Continuous Education: Journal of Science and Research, 2025)
Education in Islam has always been viewed as a means to achieve spiritual and social liberation. Although many studies discuss educational theory in Islam based on the values of liberation, most remain limited to normative approaches and have not yet integrated critical pedagogy theory within the context of Islamic education. This article aims to explore how the principles of liberation found in the Qur’an can be integrated into a critical and transformative Islamic education, and how this integration can address social injustice and oppression in society. The research employs a qualitative approach through Qur’anic text analysis and literature review on critical pedagogy. The main findings indicate that the Qur’an teaches liberation in spiritual, social, and economic dimensions, aligning with Paulo Freire’s theory of critical pedagogy, which views education as a tool to liberate individuals from oppression. The implications of these findings highlight the importance of integrating principles of liberation into the Islamic education curriculum so that education not only encompasses religious knowledge but also fosters social awareness capable of driving change. This approach is expected to produce a more relevant, participatory, and transformative form of Islamic education that contributes to creating a just society free from injustice.